Youth micropolitics in Bogotá: body, space, and word in the production of the common - Rodríguez Mejía, Jhonny Alejandro (2025)
This article examines how youth aesthetic–political practices in Bogotá’s peripheries —murals, performances, hashtags, and manifestos— operate as tactical assemblages that produce the common from conditions of precarity. Using a hermeneutic–interpretive approach, we analyze public materials (2021–2025) to trace the intersection of body, space, and word. The framework draws on De Certeau (2000), Quintana (2020), Reguillo (2003, 2010, 2017), Rancière (2014), and Das (2007). Findings indicate: (i) bodily tactics that reorder the urban sensorium; (ii) territorial disputes that rewrite memory and belonging; and (iii) minor narratives that fissure institutional grammar. We conclude these practices are not merely symbolic: they institute affective geographies and infrastructures of care, envisioning horizons of the common despite attempts at co-optation.